PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN ULANG BUSANA ADAT BALI SECARA ONLINE - N.A. Regata Satya Dewi; Driya Wiryawan; Mahatir Muhammad (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The development of technology and communication today has led to increased opportunities in the business world, this is also what underlies business pioneers to continue to develop a marketing strategy that can create and influence positive attitudes and can be profitable while increasing customer satisfaction. The purpose of this study was to determine the effect of product dimensions, price, distribution channels and promotions on the decision to repurchase Balinese traditional clothing online at the Laksmi Kebaya Boutique, Bandar Lampung. This study uses a descriptive type of research with a quantitative approach. with the object of research is the consumer at the Laksmi Kebaya Boutique Bandar Lampung, which is located in Pramuka Housing, Garden Residence block C 18 Rajabasa Bandar Lampung. The data collection method used is through literature review, and questionnaires. with a population of consumers of Laksmi Kebaya Boutique Bandar Lampung, and the number of samples is 100 people. The results of this study indicate that there is an influence between several dimensions of the marketing mix on the decision to repurchase traditional Balinese clothing online at the Laksmi Kebaya Boutique Bandar Lampung, the coefficient value is Product (0.195), Price (0.317), Distribution Channel (0.223, and Promotion (0.324).